Pengembangan Lembar Kerja Peserta Didik (LKPD) Berdiferensiasi untuk Meningatkan Keterampilan Berpikir Kritis Peserta Didik Sekolah Dasar - Rokhmaniyah, Rokhmaniyah; Indrapangastuti, Dewi; Suryandari, Kartika Chrysti; Wijayanti, Murwani Dewi; Wahyudi, Wahyudi; Chamdani, Muhamad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
There are still many elementary school teachers who are not yet able to develop digital LKPD so that learning is less interesting for students.This community service aims to: (1) improve the skills of elementary school teachers in developing digital differentiated Student Worksheet and (2) improve the critical thinking skills of elementary school students through the development of differentiated Student Worksheets. This community service was carried out at Kebakalan Elementary School, Karanggayam, Kebumen, starting with a needs analysis to obtain information and problems experienced by teachers and students. After an agreement was reached between the teachers, principals and the P2M team, workshops, training, guidance and mentoring were carried out in making differentiated digital Student Worksheets. To determine the development and success of achieving the target of at least 85% of teachers skilled in making differentiated digital Student Worksheets, monitoring and evaluation were carried out. The outputs of this community service consist of mandatory outputs in the form of: community service articles in ISSN journals, community service activity articles in print or online media, and community service activity videos. The additional outputs are in the form of Differentiated Digital Student Worksheets. Masih banyak guru SD yang belum mampu mengembangkan LKPD digital sehingga pembelajaran kurang menarik peserta didik. Pengabdian ini bertujuan untuk: (1) meningkatkan keterampilan guru SD dalam pengembangan LKPD digital berdiferensiasi dan (2) meningkatkan keterampilan berpikir kritis peserta didik SD melalui pengembangan Lembar Kerja Peserta Didik (LKPD) berdiferensiasi. Pengabdian ini dilaksanakan di SD Negeri Kebakalan, Karanggayam, Kebumen dengan diawali analisis kebutuhan untuk mendapatkan informasi dan permasalahan yang dialami para guru dan peserta didiknya. Setelah terjadi kesepakatan antara para guru, kepala sekolah dan tim P2M kemudian dilakukan kegiatan workshop, pelatihan, pembimbingan, pendampingan pembuatan LKPD digital berdiferensiasi. Untuk mengetahui perkembangan dan keberhasilan mencapai target  minimal 85 % guru terampil membuat LKPD digital berdiferensiasi, maka dilakukan monitoring dan evaluasi. Luaran pengabdian ini terdiri dari luaran wajib berupa: artikel pengabdian di jurnal ber-ISSN, artikel kegiatan pengabdian di media cetak atau online, dan video kegiatan pengabdian. Adapun luaran tambahan berupa LKPD Digital Berdiferensiasi.